Nutritional Status and Lifestyle Factors Contributing to the Regulation of Reproductive Quality in Adolescent Females - Lilis Lisnawati; Tupriliany Danefi (Inspirasi Foundation, 2023)
Introduction : Many health problems of adolescents cause a decline in their quality of life, including reproductive-related problems such as anemia, malnutrition, and obesity. Chronic nutritional dysfunction among adolescents has raised concerns since it may lead to stunting. Objective :This study examines the correlation between nutritional status and lifestyle (including habitual patterns of diet, exercises, and use of insecticides or mosquito repellent, consumption of Fe tablets and folic acid) and reproduction quality (including ages, menarche, menstrual cycle, PMS score, and length and length and severity of dysmenorrhea). Method : We used an analytic survey method with a cross-sectional study design. The population was young women aged 16-24 years, with a total of 80 people. Result : Data were not normally distributed or homogeneous; we used a non-parametric approach with the Spearman correlation test α = 0.05. The chi-square test resulted in a Sig value of 0.292 > 0.05, and the Spearman Rank correlation test results in Sig. (2-tailed) of 0.152 or a Sig (2-tailed) value of 0.152 > 0.05. Conclusion : The results indicate that the reproductive quality of adolescents is multifactorial. The nutritional status and lifestyle of adolescents are only part of the factors determining the optimization of reproductive function.